Population dynamics and stock assessment of Hilsa shad, Tenualosa ilisha (Hamilton, 1822) along the coast of Bangladesh (Bangladesh Journal of Zoology, 2021)
Stock Assessment of Tenualosa ilisha (Hamilton, 1822) were estimated using FiSAT-II software with length-frequency data collected from different landing centers. The Southeast Coast of Bay Of Bengal, Cox's Bazar. The Von Bertalanffy growth parameters Land K for the species were asymptotic length (L∞) was 51.41 cm, growth rate (K) was 0.75 year-1 and t0 = -0.2 year respectively. The estimated value of total mortality (Z) based on length converted catch curve using these growth parameters was 2.35 year-1.Natural mortality (M) based on growth parameters and mean environmental temperature (T = 27° C) was 1.00 year-1 and fishing mortality (F) was 1.35 year-1. Optimum length of hilsa at first capture (Lc=L50) was 28.36 cm TL. Growth performance indices (ϕ') was 3.30. The estimated value of the exploitation rate (E) using the length-converted catch curve was 0.57. The recruitment pattern of this species was continuous and two peaks per year. The present investigation clearly showed the over fishing (E > 0.50) condition for T. ilisha in Bangladesh. The estimated length-weight relationship for the combined sex was found to be W = 0.0109 L3. Virtual population analysis (VPA) showed that the maximum fishing mortality occurring in the length between 30 to 35 cm with a maximum value in the length of 32 cm that repeatedly indicate high fishing mortality in the T. ilisha. The generalized length-weight relationship was fitted with the pooled data of all monthly samples were BW = 0.029 TL2.718 (R2= 0.833) respectively. The results revealed that all length-weight relationships were highly correlated (r > 0.993). Maximum sustainable yield (MSY) was estimated as 435,554 t.Bangladesh J. Zool. 48(2): 231-241, 2020